Molecular Machines Involved in Peroxisome Biogenesis and Maintenance 2014
DOI: 10.1007/978-3-7091-1788-0_14
|View full text |Cite
|
Sign up to set email alerts
|

Protein Transport In and Out of Plant Peroxisomes

Abstract: Plant peroxisomes house conserved functions such as β-oxidation and hydrogen peroxide decomposition along with specialized tasks including hormone metabolism and photorespiration. Phenotypes stemming from defects in these pathways have been exploited to isolate and characterize peroxisome-defective mutants in the reference plant Arabidopsis thaliana. Because peroxisome function is essential for plant viability, partial loss-of-function alleles have been frequently recovered from forward genetic screens. Analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 94 publications
0
20
0
Order By: Relevance
“…pex2-1 and pex10-2 are the first alleles of PEX2 and PEX10 to emerge from forward genetic screens for peroxisome defects in Arabidopsis. The isolation of pex2-1, which lacks dramatic physiological defects, adds to growing evidence that microscopy-based screens (Mano et al, 2006;Goto et al, 2011;Burkhart et al, 2013) can identify peroxisome-defective mutants with physiological defects too subtle to emerge from more common screens for reduced b-oxidation (for review, see Bartel et al, 2014a).…”
Section: Discussionmentioning
confidence: 99%
“…pex2-1 and pex10-2 are the first alleles of PEX2 and PEX10 to emerge from forward genetic screens for peroxisome defects in Arabidopsis. The isolation of pex2-1, which lacks dramatic physiological defects, adds to growing evidence that microscopy-based screens (Mano et al, 2006;Goto et al, 2011;Burkhart et al, 2013) can identify peroxisome-defective mutants with physiological defects too subtle to emerge from more common screens for reduced b-oxidation (for review, see Bartel et al, 2014a).…”
Section: Discussionmentioning
confidence: 99%
“…A reverse-genetic screen for EMBRYO-DEFECTIVE (EMB) genes identified two insertional mutations in PEX1 (emb2817-1 and emb2817-2) that confer embryos arresting at the preglobular stage (http://www.seedgenes.org/; Muralla et al, 2011). Although mutants in almost all predicted single-gene peroxins have been isolated in forward-genetic screens for peroxisomal defects in Arabidopsis (for review, see Bartel et al, 2014), viable pex1 mutants have not been reported in plants. Here, we describe two Arabidopsis mutants in PEX1, pex1-2 and pex1-3, that display distinct peroxisome-related defects and harbor missense mutations in the region encoding the PEX1 D2.…”
mentioning
confidence: 99%
“…At a cellular level, defects in peroxisomal size, positioning, and matrix protein import can be visualized by tagging GFP with a PTS, which also has formed the basis of screens for mutants with peroxisome defects (Mano et al, 2006;Burkhart et al, 2013;Rinaldi et al, 2016). Because PTS2 cleavage occurs after import, mutations in peroxin genes often impair PTS2 processing (for review, see Bartel et al, 2014). The PTS2-processing protease DEG15 is a PTS1 protein (Helm et al, 2007), and so PTS2-processing defects can reflect PTS1 and/or PTS2 import defects.…”
mentioning
confidence: 99%
See 2 more Smart Citations